Adults and children with anaphylaxis in the emergency room: why it is not recognized?. Issue 5 (October 2018) - Aun, Marcelo V.; Kalil, Jorge; Giavina-Bianchi, Pedro
Abstract : Purpose of review: Despite many international guidelines have been published in the last 10 years, anaphylaxis continues to be underdiagnosed, undernotified, and undertreated. Anaphylactic reactions in adults and children in emergency departments are frequently not recognized, leading to underutilization of epinephrine, and a higher risk of death. Recent findings: A few studies have been recently published showing that educational intervention for both physicians and other healthcare professionals improve diagnosis and treatment of anaphylaxis. Moreover, the new International Classification of Diseases, 11th edition improved classification of anaphylaxis, making it easier to be notified. Summary: Anaphylaxis is a life-threatening hypersensitivity reaction that is most frequently seen by emergency physicians and nurses than allergists or immunologists. Education seems to be best strategy to improve management of this severe condition.